Decreasing energy use and influence to environment by radiant panel heating using different energy sources. (15th January 2015) - Bojić, Milorad; Cvetković, Dragan; Bojić, Ljubiša
Highlights: Currently in Serbia the use of GSHP over natural gas boiler and GSHP with PV is not justified. The impact of the embodied energy, embodied carbon, and investment is included in this paper. The operation of this house is simulated by software EnergyPlus. The newly-developed floor-ceiling radiant heating has the best performances. In future with decrease in R, the panel heating by GSHP may have lower total energy consumption than that by natural gas. Abstract: In Serbia, radiant heating is increasingly used. Also, in Serbia, the largest portion of produced electricity is from the fossil fuels which results in a high value of primary energy consumption coefficient ( R ). This situation raises the question of the justification of the use of ground sources heat pump (GHSP) over natural gas boiler and GSHP with PV array. Also, the impact of the embodied energy and embodied carbon was included in this paper. The operation of this house is simulated by software EnergyPlus. The results indicated that the newly-developed floor-ceiling radiant heating system has the best performances and classical ceiling heating has the worst performances. However in future with decrease of R, it is shown that the panel heating powered by GSHP may have lower total energy consumption than that of such a system powered by natural gas. For the wall panel heating, this would happen for the highest value of R, while in the case of the ceiling heating, it would appear for the lowest value of R .